Gender and aesthetics : an introduction - Korsmeyer, Carolyn (Understanding feminist philosophy., 2004)
Feminist approaches to art are extremely influential and widely studied across a variety of disciplines, including art theory, cultural and visual studies, and philosophy. Gender and Aesthetics is an introduction to the major theories and thinkers within art and aesthetics from a philosophical perspective, carefully introducing and examining the role that gender plays in forming ideas about art. It is ideal for anyone coming to the topic for the first time. Organised thematically, the book introduces in clear language the most important topics within feminist aesthetics: * Why were there so.